Transmission of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) in a Patient Transport Van. (23rd April 2021) - Jones, Lucas D; Chan, Ernest R; Zabarsky, Trina F; Cadnum, Jennifer L; Navas, Maria E; Redmond, Sarah N; Kovach, Jeffrey D; Linger, Marlin; Rutala, William A; Zimmerman, Peter A; Donskey, Curtis J
Abstract: We report 2 episodes of potential SARS-CoV-2 transmission from infected van drivers to passengers despite masking and physical distancing. Whole-genome sequencing confirmed relatedness of driver and passenger SARS-CoV-2. With the heater operating, fluorescent microspheres were transported by airflow >3 meters from the front to the back of the van.